PENGARUH DANA PERIMBANGAN DAN DANA DESA TERHADAP PENGURANGAN TINGKAT KEMISKINAN PADA KABUPATEN DI PROVINSI NUSA TENGGARA BARAT - Aditya Dia'ullail Fachra (Laboratorium Riset Ekonomi, 2024)
This study aims to examine the influence of the Balance Fund in the form of General Allocation Fund, Special Allocation Fund, Revenue Sharing Fund, as well as Village Fund on poverty levels in West Nusa Tenggara Province districts. The type of data used in this study is secondary data obtained from the publication of BPS and the Director General of Financial Balance with a data period from 2017 to 2023. The objects involved in this study are 8 districts in West Nusa Tenggara Province. The analysis method used in this study is a panel data regression analysis method with a Fixed Effect Model (FEM) analysis model. The results of the research data test showed that partially the Balance Fund variable in the form of General Allocation Fund had a negative and significant effect on the poverty rate in the districts in West Nusa Tenggara Province, Revenue Sharing Fund has a negative and significant effect on the poverty rate, Special Allocation Fund has a negative and significant effect on the poverty rate, and the Village Fund variable also has a negative and significant effect on the poverty rate in the district in West Nusa Tenggara Province. Simultaneously, the Balance Fund variable consisting of General Allocation Fund, Special Allocation Fund, Revenue Sharing Fund, as well as Village Fund variable had a significant effect on the level of poverty in the district in West Nusa Tenggara Province.